SPE International Symposium on Oilfield Chemistry 2005
DOI: 10.2118/93357-ms
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin Crystal and Deposition Control By Emulsification

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis laboratory investigation considers the effects of emulsions (via adding surfactants) and the formation and deposition of paraffin wax. This study relates the properties of added surfactant and emulsion characteristics with their wax deposition tendency. Parameters considered include the surfactant HLB (Hydrophilic Lipophilic Balance), molecular weight, and surfactant concentration. Two different series of commercial nonionic surfactants are included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In general, an increase in crude oil shear or flow rate will decrease the rate of deposition (Singh, Venkatesan et al 2000;Hoteit, Banki et al 2008). Ahn et al, (Ahn, Wang et al 2005) suggested that the presence of emulsifiers may be able to selectively inhibit the deposition of higher molecular weight paraffin components (Ahn, Wang et al 2005). Visintin et al (Visintin, Lapasin et al 2005) concluded that crude oil flowing in the pipeline below its WAT temperature will not necessarily block the pipeline, given the fact that the fluid is always in movement (Venkatesan, Singh et al 2002;Visintin, Lapasin et al 2005).…”
Section: Fluid Flow In Process Linesmentioning
confidence: 99%
“…In general, an increase in crude oil shear or flow rate will decrease the rate of deposition (Singh, Venkatesan et al 2000;Hoteit, Banki et al 2008). Ahn et al, (Ahn, Wang et al 2005) suggested that the presence of emulsifiers may be able to selectively inhibit the deposition of higher molecular weight paraffin components (Ahn, Wang et al 2005). Visintin et al (Visintin, Lapasin et al 2005) concluded that crude oil flowing in the pipeline below its WAT temperature will not necessarily block the pipeline, given the fact that the fluid is always in movement (Venkatesan, Singh et al 2002;Visintin, Lapasin et al 2005).…”
Section: Fluid Flow In Process Linesmentioning
confidence: 99%
“…Dynamic wax deposition describes the formation of gel and the amount of wax deposited on pipeline walls, taking into account effects such as shear and flow rate (Ahn et al, 2005). Dynamic wax deposition describes the formation of gel and the amount of wax deposited on pipeline walls, taking into account effects such as shear and flow rate (Ahn et al, 2005).…”
Section: Phase Behaviormentioning
confidence: 99%
“…into account the effect of shear rate, flow rate, water cut, etc. This simulation requires a knowledge of wax precipitation, and is obtained by thermodynamic modeling as discussed earlier (Ahn et al, 2005).…”
Section: Need For Modeling Wax Precipitationmentioning
confidence: 99%